A Rapid and Versatile Assay for Ago2‐Mediated Cleavage by Using Branched Rolling Circle Amplification. (8th January 2016) - Hesse, Marlen; Arenz, Christoph
Abstract: Micro RNA (miRNA) research has evolved into an essential part of investigating gene regulation in which deregulation of numerous miRNAs is associated with various cellular dysfunction and diseases. Here, we describe a rapid and homogenous assay for Ago2‐mediated target RNA cleavage, based on branched rolling circle amplification (BRCA). In particular, the ability to investigate small molecule binders for inhibition of miRNA function is within the potential of our assay. This method uses no artificial fluorescence labeling of RNA components, which can be an advantage in screening of potential inhibitors. To visualize cleavage of RNA substrate by Ago2, we developed a two‐step assay composed of Ago2‐mediated cleavage and BRCA‐based detection. The assay is cost‐effective and practicable and can be performed in 96‐well format by using a standard qPCR machine. Abstract : Label‐free cleavage assay : We have developed a two‐step assay for Ago2‐mediated RNA cleavage involving branched rolling‐circle amplification (BRCA)‐based detection. Upon cleavage by the Ago2 enzyme, the new 3′‐end of the cleaved mRNA‐like substrate serves as a primer for a DNA polymerase, thus enabling BRCA.